ANALYSIS OF THE USE OF BASKETBALL IN UKRAINE AS A TOOL FOR SOCIAL INTEGRATION AND PSYCHOLOGICAL ADAPTATION: THE EXPERIENCE OF THE “BASKETBALL-KTN” PROJECT - Galan, Iaroslav (ТНПУ ім. В. Гнатюка, 2025)
Within the framework of the European Union ERASMUS+ Sport project entitled “Creating a hybrid model of a knowledge transfer network for the promotion and development of basketball / BASKETBALL-KTN,” a sociological study was conducted on the impact of basketball programs on the social integration and psychological recovery of young athletes, particularly, in Ternopil and Chernivtsi regions. The publication focuses on the analysis of the results of a survey of young basketball players. The project in Ukraine is implemented by the public organization “YOUTH. SCIENCE. SPORT. HEALTHY MOVEMENT OF UKRAINE” and is co-funded by the European Union. The respondents to the survey were athletes under the age of 18, parents, and future coaches and trainers. Based on the results of the survey, it is recommended to implement comprehensive approaches, including the development of sports infrastructure, training of qualified coaches, and active use of digital technologies, which together will contribute to more effective adaptation of young people and increase their motivation to play sports.
Keywords: basketball; social integration; young athletes; youth; project